An Enhanced IoT Based Tracing and Tracking Model for COVID -19 Cases - Rajasekar, Sakthi Jaya Sundar (SN computer science, 2021)
The COVID-19 pandemic has alarmed the world nations to impose strict curfews and emergencies to prevent the social transmission of the disease. In order to achieve this, effective Tracing and Tracking of the suspected COVID-19 cases need to be achieved. In view of the enormous number of cases being recorded each day, this process couldn’t be performed effectively with simple manual tracing. Hence, we have proposed an Internet of Things (IoT) based automated Tracing and Tracking method for identification of the possible contacts with deployment of cost-effective RFID Tags and the mobile of the individuals which act as a reader. Thereby, tracing of persons who have crossed the subject would be possible even without the knowledge of the suspected cases. This would enable cent percent quarantine of possible primary and secondary contacts and monitoring of the same by the administrative agencies. This would augment the nations’ capability of managing the pandemic.